Implementation of the principle of strict liability in environmental law: A case study of Cesium-137 Radiation Exposure in the Modern Cikande Industrial Area - Annisa Indah Nuari; Shofiyatu Jahra; Aryoko Abdurrachman (Privietlab, 2025)
This study aims to examine the government's efforts to enforce environmental law as a form of legal protection for communities and workers affected by exposure to Radioactive Cesium-137 in the Modern Cikande Industrial Area. This study employs a qualitative descriptive method with a normative juridical and case study approach. The findings indicate that the company responsible for exposure to Radioactive Cesium-137 can be held legally accountable based on the principle of strict liability. The conclusion of this study indicates that the government needs to enhance the supervision of industrial activities that are vulnerable to pollution from hazardous and toxic waste materials. Furthermore, the government must enforce strict legal measures regarding environmental violations in accordance with the principle of strict liability and applicable laws and regulations.